Burial of the Roumanian queen mother. Behind the coffin king Carol, princess Elisabeth, Ileana von Habsburg and crown prince Michael. Text on the back
Burial of the Roumanian queen mother. Behind the coffin king Carol, princess Elisabeth, Ileana von Habsburg and crown prince Michael. Text on the back.